2014
DOI: 10.1016/j.bjid.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 7- and 30-day mortality in pediatric intensive care unit patients with cancer and hematologic malignancy infected with Gram-negative bacteria

Abstract: Shock was a predictor of 7- and 30-day mortality, and colonization by multidrug resistant-Gram-negative bacteria was an important risk factor for 30-day mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In our study, the overall incidence of bacteremia during the early transplant period after HDCT/auto-SCT was 7.1%, which was lower than results from adult studies [13,22] and similar to the 7% incidence of overall bacteremia seen 0-30 days post-transplant in a SJCRH cohort [21]. This incidence of bacteremia might be acceptable considering the nature of treatment and the usual prognosis for tumors included in this study; however, the MDR bacteremia might be a significant clinical problem [10,23]. In this study, the incidence of MDR bacteria, particularly ESBL-producing Escherichia coli, appeared to increase over time, and four patients died from MDR bacterial infection.…”
Section: Discussionmentioning
confidence: 41%
“…In our study, the overall incidence of bacteremia during the early transplant period after HDCT/auto-SCT was 7.1%, which was lower than results from adult studies [13,22] and similar to the 7% incidence of overall bacteremia seen 0-30 days post-transplant in a SJCRH cohort [21]. This incidence of bacteremia might be acceptable considering the nature of treatment and the usual prognosis for tumors included in this study; however, the MDR bacteremia might be a significant clinical problem [10,23]. In this study, the incidence of MDR bacteria, particularly ESBL-producing Escherichia coli, appeared to increase over time, and four patients died from MDR bacterial infection.…”
Section: Discussionmentioning
confidence: 41%
“…Pseudomonas aeruginosa , an opportunistic Gram-negative bacillus, is a frequent cause of hospital-acquired infections, including ventilator-associated pneumonia 1 and catheter infections in immunocompromised patients. 2 The progressive deterioration of the lungs due to chronic P. aeruginosa infection and the resulting persistent inflammation are currently the main causes of morbidity and mortality in patients with cystic fibrosis. 3 , 4 P. aeruginosa produces factors associated with intracellular communication and extracellular virulence that are globally regulated by well-defined quorum-sensing (QS) systems that determine bacterial pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies regarding sepsis and outcomes in oncological and nononcological patients are inconsistent. While some studies have suggested that their outcomes may be similar,22,23 others have reported an up to a 30% higher risk of death of septic oncological pediatric patients 11,18,20,21,24. The prognosis may worsen further in patients with neutropaenia, although the available evidence for this is also conflicting 16,22,25–27…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have suggested that their outcomes may be similar, 22,23 others have reported an up to a 30% higher risk of death of septic oncological pediatric patients. 11,18,20,21,24 The prognosis may worsen further in patients with neutropaenia, although the available evidence for this is also conflicting. 16,22,[25][26][27] In this group of oncological patients, the presence of sepsis and neutropenia were associated with a more than 3-fold increase in mortality (P = 0.0034 and 0.0032, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation